Transcriptome response of a new serotype of avian type Klebsiella varicella strain to chicken sera. (July 2022) - Yin, Lei; Shen, Xuehuai; Zhang, Danjun; Zhao, Ruihong; Dai, Yin; Hu, Xiaomiao; Wang, Jieru; Hou, Hongyan; Pan, Xiaocheng; Qi, Kezong
Abstract: Klebsiella variicola is a newly discovered pathogen of zoonotic importance, commonly causing serious systemic infection via the bloodstream route. However, the mechanism by which K. variicola survives and grows in the bloodstream is poorly understood. In a previous study, a strain of Klebsiella causing chicken bloodstream infection was obtained, and whole genome sequencing showed that it was a new ST174 type K. variicola . Therefore, the present study aimed to determine the molecular mechanism underlying the survival and development of K. variicola in host serum. First, we compared the transcriptomes of K. variicola grown in Luria-Bertani broth and chicken serum. We sequenced six RNA libraries from the two groups, each library had three repeats. A total of 1046 differentially expressed genes were identified. Functional annotation analysis showed that the differentially expressed genes are mainly involved in adaptive metabolism, biosynthesis pathways (including biosynthesis of siderophore group nonribosomal peptides and lipopolysaccharide (LPS) biosynthesis), stress resistance, and several known virulence regulatory systems (including the ABC transporter system, the two-component signal transduction system and the quorum sensing system). These genes are expected to contribute to the adaptation and growth of K. variicola in host birds. This analysis provides a new insight into the pathogenesis of K. variicola . Highlights: Klebsiella variicola rapidly adapts to chicken serum. The iron is essential for the growth of K. variicola in chicken serum. The chicken serum was a stress environment for K. variicola . K. variicola growth in serum affects the virulence regulatory system.